CompTIA A+ certification study guide : (exams 220-1101 & 220-1102) - Wempen, Faithe (McGraw-Hill, 2022)
With 400 accurate practice questions and hands-on exercises, CompTIA A+ Certification Study Guide, Eleventh Edition (Exams 220-1101 & 220-1102) teaches you what you need to know--and shows you how to prepare--for these challenging exams. This bestselling self-study guide has been fully revised to offer 100% coverage of all current objectives for both exams. This integrated study system is based on proven methodology. Step-by-step exercises, end-of-chapter self-tests, and special design elements sections reinforce salient points and aid in retention. This up-to-date edition features new or expanded coverage of cloud and virtualization, Windows 10, Linux, mobile devices and operating systems, enhanced security, and advanced software troubleshooting.